2012
DOI: 10.1002/anie.201205604
|View full text |Cite
|
Sign up to set email alerts
|

A Nonmetal Approach to α‐Heterofunctionalized Carbonyl Derivatives by Formal Reductive XH Insertion

Abstract: Keeping it organic: A direct synthesis of α-alkoxy and α-amino ester derivatives by direct reductive coupling of widely available, stable α-keto esters and protic pronucleophiles is described (see scheme; X = OR, NR(2)). The method serves as a convenient nonmetal alternative to X-H insertion by diazo decomposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 60 publications
2
32
0
1
Order By: Relevance
“…2 We have shown that these Kukhtin-Ramirez adducts further react to incorporate a range of N -, O -, and C -based protic pronucleophiles with expulsion of a phosphine oxide by-product. 3,4 The process likely proceeds in stepwise fashion, initiated by proton transfer from the protic pronucleophile to the Kukhtin-Ramirez adduct, followed by Arbuzov-like displacement of the phosphine oxide leaving group. This reaction sequence therefore represents a convenient one pot process for access to a range of α–functionalized carbonyl compounds from readily available reagents and precursors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 We have shown that these Kukhtin-Ramirez adducts further react to incorporate a range of N -, O -, and C -based protic pronucleophiles with expulsion of a phosphine oxide by-product. 3,4 The process likely proceeds in stepwise fashion, initiated by proton transfer from the protic pronucleophile to the Kukhtin-Ramirez adduct, followed by Arbuzov-like displacement of the phosphine oxide leaving group. This reaction sequence therefore represents a convenient one pot process for access to a range of α–functionalized carbonyl compounds from readily available reagents and precursors.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction sequence therefore represents a convenient one pot process for access to a range of α–functionalized carbonyl compounds from readily available reagents and precursors. 3,4 …”
Section: Discussionmentioning
confidence: 99%
“…Efforts to circumvent these hazards include the use of latent diazo compounds,10b, 13 sulfur,14 or iodonium ylides15 and, more recently, cyclopropenes16 among others 17. Nevertheless, examples of CH insertion employing these surrogates remain limited,18 including for alkylidenecarbenes derived from α‐elimination of the corresponding iodonium tetrafluoroborates 18d…”
Section: Methodsmentioning
confidence: 99%
“…[46] , 72 优先与 73 进行质子转移生成中间体 74, 随 后氨基甲酸根亲核进攻释放出膦氧化合物的同时得到 氨基甲酸酯化合物 75, 其在碱催化下闭环最终得到噁 唑啉二酮产物(Scheme 16). 由于 Kukhtin-Ramirez 加合 物 72 的高亲核反应活性 [47] , 此羧化反应只需在 101 kPa 的二氧化碳气氛下就可顺利进行.…”
Section: 二氧化碳作为储量丰富、廉价易得的可再生碳一资unclassified